High-temperature-corrosion-resistant cylinder structure for heat treatment of graphite negative electrode material and preparation method
By designing a high-temperature corrosion-resistant cylinder structure, the problems of unreasonable thermal engineering system and high-temperature sulfurization corrosion in the preparation process of graphite negative electrode materials for lithium-ion batteries are solved, and efficient heat treatment and the effect of extending the service life of the cylinder is achieved.
Patent Information
- Application Number
- CN202411502249.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-07
AI Technical Summary
In the existing lithium-ion battery graphite negative electrode material preparation process, the unreasonable thermal system leads to serious energy waste, low equipment processing capacity and low production efficiency; at the same time, the traditional tunnel kiln calcining process is difficult to control the temperature in the kiln, resulting in large burning of materials. , the specific surface area of the product increases, and the cylinder has a short service life in high-temperature vulcanization corrosion.
A high-temperature corrosion-resistant cylinder structure for heat treatment of graphite negative electrode materials is designed, including a substrate layer, an adhesive transition layer, a corrosion-resistant layer and a sealing layer. Each layer is formed through aluminized treatment and plasma thermal spraying technology to improve the cylinder body. Anti-sulfurization corrosion properties.
The high-temperature vulcanization corrosion of the metal cylinder by the pre-carbonization heat treatment process of the graphite anode material of lithium-ion batteries at 900-1100°C, extending the service life of the cylinder and improving production efficiency.
Smart Images

Figure CN119392154A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of heat treatment of graphite negative electrode materials for lithium-ion batteries, and in particular to a high-temperature corrosion-resistant cylinder structure for heat treatment of graphite negative electrode materials and a preparation method thereof. Background Art
[0002] At present, the graphite negative electrode materials used on a large scale in the lithium-ion battery industry are usually coated and granulated before graphitization to improve their electrochemical properties, and then pre-carbonized to reduce the volatile matter of the material and increase the material tap density to increase the material loading capacity and operation safety of the graphitization process.
[0003] The coating granulation-pre-carbonization section in the preparation process of graphite negative electrode materials for lithium-ion batteries adopts the following process: first, petroleum coke / needle coke and asphalt are crushed to 8-10 microns and 2-3 microns respectively through a crushing device; then the two are mixed in a certain proportion and sent to a coating reactor. A resistance wire is installed outside the reactor to transfer heat to the material in the reactor through the wall of the vessel, and the temperature of the material is controlled according to a certain temperature control curve to complete the softening, melting and coating and carbonization of the asphalt. Due to the heat transfer limitation of the equipment, the maximum temperature of the material can generally only reach 650°C, and some aromatic hydrocarbons in the asphalt that require a high temperature of >650°C to decompose cannot be decomposed. The material coming out of the coating reactor needs to be cooled to <100°C through the cooling kettle of the water-cooled jacket indirect cooling device, and then sent to a roller kiln or a tunnel kiln to be heated to 1000°C to further decompose and carbonize the aromatic hydrocarbons in the asphalt, and then sent to a graphitization furnace to complete graphitization at about 3000°C. After cooling, it is treated to obtain the product carbon-based lithium battery graphite negative electrode material.
[0004] The existing lithium-ion battery graphite negative electrode material coating granulation-precarbonization process has the following problems:
[0005] 1. The thermal system is unreasonable. The material is heated to 650°C in the coating reactor. When discharging the material, it needs to be cooled to room temperature by indirect water cooling through the cooling kettle, and then sent to the roller kiln or tunnel kiln, reheated to about 1000°C, and then cooled to room temperature, resulting in serious energy waste.
[0006] 2. As far as coated granulation is concerned, the main thermal equipment, the reactor and the cooling kettle, are intermittently operated equipment, and the processing capacity of a single device is low and the labor cost is high; due to heat transfer limitations, the processing capacity of a single device is small and the production efficiency is low.
[0007] 3. As far as pre-carbonization is concerned, the traditional tunnel kiln calcination process is adopted. The tunnel kiln is an internal heating equipment, the temperature inside the kiln is difficult to control, and the temperature difference in the height direction is large; the material is placed in a crucible for indirect heating, the loading and unloading process is complicated, the operating environment and material loss are large; the oxygen content at the top of the crucible is high, the material burns out and causes the specific surface area of the product to increase.
[0008] For this purpose, some related technologies disclose a rotary kiln, which is an indirect heating rotary kiln heated by an external heating furnace, that is, the heating source is outside the cylinder, the pre-treated material is inside the cylinder, the temperature of the coating granulation is 200-650°C, and the heat treatment temperature of the pre-carbonization stage is 900-1100°C. Production practice shows that the sulfur in the material below 850°C corrodes the heat-resistant alloy slowly, and the service life of the cylinder is long, which can meet production needs; while when the temperature exceeds 900°C, H2, CH4, CO, CO2 and H2S gases are produced when heated, and sulfidation corrosion is accelerated sharply. Corrosion protection must be carried out to ensure the long-term use of the rotary kiln cylinder.
[0009] The drum of the rotary kiln is mostly made of heat-resistant alloys. Commonly used heat-resistant alloys include 310S, 600, 601, 602CA, RA330, GH2747 and other high-nickel-chromium alloys (Ni≥20%). These alloys have good high-temperature oxidation resistance, but lack protection against high-temperature sulfidation. Especially for high-nickel alloys, the melting point of the nickel-nickel sulfide mixture is only about 630°C, so the corrosion rate of high-nickel alloys exceeds that of general alloy materials under conditions exceeding 630°C. Production practice data show that under the temperature condition of 1000°C±50°C, when the sulfur content in the solid coke powder is about 1%, the corrosion rate of the 310S drum is ≥12mm / a. Even if the sulfur content in the solid coke powder is reduced to ≤0.5%, it is difficult to avoid the high-temperature sulfidation corrosion of the drum by hydrogen sulfide produced during the carbonization process.
[0010] Therefore, how to ensure that the cylinder can withstand sulfide corrosion under the condition of 900-1100℃ is a difficult problem to ensure the long-term use of the cylinder. In the past, there were few public reports on high-temperature sulfide corrosion protection technology in reducing atmosphere at this operating temperature.
[0011] For example, in some related technologies, the sulfidation corrosion resistance of MCrAlY coating at 700°C can be more than doubled by adding rare earth elements to the coating, but there are no reports on sulfidation corrosion resistance at 1000°C. Summary of the invention
[0012] The embodiment of the present application provides a high-temperature corrosion-resistant cylinder structure and a preparation method for heat treatment of graphite negative electrode materials, which can increase the service life of the cylinder of a rotary kiln against high-temperature sulfidation corrosion at 900-1100°C.
[0013] In the first aspect, a high-temperature corrosion-resistant cylinder structure for heat treatment of graphite negative electrode materials is provided, which includes a base layer, a bonding transition layer, a corrosion-resistant layer and a sealing layer arranged in sequence, wherein the base layer includes a base layer body and an aluminized layer formed on the surface of the base layer body, the aluminized layer is located between the base layer body and the bonding transition layer, and the thermal expansion coefficient of the bonding transition layer is between the thermal expansion coefficients of the base layer and the corrosion-resistant layer.
[0014] In some embodiments, the material of the substrate layer includes one or more of Fe-based high-temperature alloy, Ni-based high-temperature alloy and Co-based high-temperature alloy;
[0015] And / or, the thickness of the base layer is ≥10 mm.
[0016] In some embodiments, the average Ni content in the base layer is ≥20%, and the average Cr content is ≥25%.
[0017] In some embodiments, the Al content in the aluminized layer is ≥ 15%;
[0018] And / or, the thickness of the aluminized layer is 50-300 μm.
[0019] In some embodiments, the material of the bonding transition layer includes one or more of Ni Cr alloy, CoCr alloy, FeCrAlY alloy, NiCrAlY alloy, CoCrAlY alloy and NiCrCoAlY alloy;
[0020] And / or, the thickness of the bonding transition layer is 50-2002 μm;
[0021] And / or, the melting point of the bonding transition layer is ≥1300°C;
[0022] And / or, the thermal expansion coefficient of the bonding transition layer is (12-15)×10 -6 K -1 .
[0023] In some embodiments, the material of the corrosion-resistant layer is one or more of Al2O3, ZrO2, Al N, BN, Si3N4, SiC, NiAl alloy, CoAl alloy, Al Mo alloy and Al MoSi alloy;
[0024] And / or, the thickness of the corrosion-resistant layer is 50-2002 μm;
[0025] And / or, the melting point of the corrosion-resistant layer is ≥1400°C, and the decomposition temperature is ≥1400°C.
[0026] In some embodiments, the material of the sealing layer includes one or more of organic silicon, inorganic silicon and asphalt-based aluminum paste;
[0027] And / or, the sealing layer has a thickness of 30-1002 μm.
[0028] In a second aspect, a method for preparing a high temperature corrosion resistant cylinder structure for heat treatment of a graphite negative electrode material as described above is provided, comprising:
[0029] On the base layer, aluminizing is performed by a solid powder embedding method, so that the base layer forms a base layer body and an aluminizing layer;
[0030] The surface of the aluminized layer is subjected to sandblasting treatment so as to achieve a designed roughness;
[0031] Spraying on the aluminized layer through a plasma thermal spraying process to form a bonding transition layer;
[0032] Spraying on the bonding transition layer through a plasma thermal spraying process to form a corrosion-resistant layer;
[0033] The sealing agent is sprayed or brushed on the corrosion-resistant layer, and then a pre-oxidation heat treatment is performed to obtain a sealing layer.
[0034] In some embodiments, the designed roughness Rz is 25-100 μm;
[0035] And / or, the temperature of the pre-oxidation heat treatment is 600-1050°C.
[0036] In a third aspect, a rotary kiln is provided, which includes a high temperature corrosion resistant cylinder structure for heat treatment of graphite negative electrode materials as described above.
[0037] The beneficial effects of the technical solution provided by this application include:
[0038] In the cylinder structure designed in the embodiment of the present application, after the surface of the base layer is treated with aluminizing, an aluminizing layer is formed to increase the Al content on the surface of the base layer, thereby improving the anti-sulfidation corrosion performance of the base layer, that is, Al2O3 is formed on the surface of the base material to prevent sulfidation corrosion. A bonding transition layer is designed between the base layer and the corrosion-resistant layer, and the adhesion bonding force is improved by the bonding transition layer to firmly fix the corrosion-resistant layer on the base layer, and the thermal expansion coefficient of the bonding transition layer is between the thermal expansion coefficients of the base layer and the corrosion-resistant layer, so that the bonding transition layer has a key connecting role in the cylinder structure, avoiding the problem of low bonding strength with the base layer and easy falling off caused by the large difference in thermal expansion coefficient between the corrosion-resistant layer and the base layer. The corrosion-resistant layer resists high-temperature sulfidation corrosion. The sealing layer fills the holes of the corrosion-resistant layer to ensure that hydrogen sulfide is difficult to penetrate the corrosion-resistant layer to corrode the base layer or the bonding transition layer at high temperature.
[0039] The cylinder structure designed in the present application has mutually dependent functions of each layer. The sealing layer and the corrosion-resistant layer are used to shield the external hydrogen sulfide from penetrating into the bonding transition layer. The bonding transition layer is used to ensure the adhesion stability of the corrosion-resistant layer. The aluminized layer slows down the unstable shedding of the bonding transition layer caused by the corrosion of the base layer. At the same time, the aluminized layer also reduces the outward migration rate of the base metal ions, thereby preventing the corrosion products generated in the outermost layer of the cylinder structure from damaging the sealing layer and the corrosion-resistant layer from the external thermal stress. Therefore, the present application strengthens the corrosion resistance of each layer, fully delays the corrosion rate of each layer, and ensures the stability of each structural layer, thereby achieving a long service life of the cylinder.
[0040] The results of the sulfidation corrosion test at 900-1100°C show that, compared with a single metal alloy structure cylinder, the cylinder structure designed in the present application can greatly reduce the high-temperature sulfidation corrosion of the metal cylinder during the pre-carbonization heat treatment process of the lithium-ion battery graphite negative electrode material at 900-1100°C, greatly extending the service life of the cylinder. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0042] Figure 1 Schematic diagram of the high temperature corrosion resistant cylinder structure for heat treatment of graphite negative electrode material provided in an embodiment of the present application.
[0043] In the figure: 1, substrate layer; 10, substrate layer body; 11, aluminized layer; 2, bonding transition layer; 3, corrosion resistant layer; 4, sealing layer. DETAILED DESCRIPTION
[0044] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0045] See also Figure 1As shown, an embodiment of the present application provides a high-temperature corrosion-resistant cylindrical structure for heat treatment of graphite negative electrode materials, which includes a base layer 1, a bonding transition layer 2, a corrosion-resistant layer 3 and a sealing layer 4 arranged in sequence, wherein the base layer 1 includes a base layer body 10 and an aluminized layer 11 formed on the surface of the base layer body 10, and the aluminized layer 11 is located between the base layer body 10 and the bonding transition layer 2. It can be understood that the surface of the base layer 1 is aluminized by solid powder embedding method to form a base layer body 10 that is not aluminized, and an aluminized layer 11 infiltrated with aluminum, and the thermal expansion coefficient of the bonding transition layer 2 is between the thermal expansion coefficients of the base layer 1 and the corrosion-resistant layer 3.
[0046] In the cylinder structure designed in the embodiment of the present application, after the surface of the base layer 1 is aluminized, an aluminized layer 11 is formed to increase the Al content on the surface of the base layer 1, thereby improving the anti-sulfidation corrosion performance of the base layer 1, that is, Al2O3 is formed on the surface of the base material to prevent sulfidation corrosion. A bonding transition layer 2 is designed between the base layer 1 and the corrosion-resistant layer 3, and the adhesion bonding force is improved by the bonding transition layer 2 to firmly fix the corrosion-resistant layer 3 on the base layer 1, and the thermal expansion coefficient of the bonding transition layer 2 is between the thermal expansion coefficients of the base layer 1 and the corrosion-resistant layer 3, so that the bonding transition layer 2 has a key role in connecting the upper and lower parts in the cylinder structure, avoiding the problem that the corrosion-resistant layer 3 has a low bonding strength with the base layer 1 and is easy to fall off due to the large difference in thermal expansion coefficient between the base layer 1 and the corrosion-resistant layer 3. The corrosion-resistant layer 3 resists high-temperature sulfidation corrosion. The sealing layer 4 fills the holes of the corrosion-resistant layer 3 to ensure that hydrogen sulfide is difficult to penetrate the corrosion-resistant layer to corrode the base layer 1 or the bonding transition layer 2 at high temperature.
[0047] The cylinder structure designed in the present application has mutually dependent functions of each layer. The sealing layer and the corrosion-resistant layer are used to shield the external hydrogen sulfide from penetrating into the bonding transition layer. The bonding transition layer is used to ensure the adhesion stability of the corrosion-resistant layer. The aluminized layer slows down the unstable shedding of the bonding transition layer caused by the corrosion of the base layer. At the same time, the aluminized layer also reduces the outward migration rate of the base metal ions, thereby preventing the corrosion products generated in the outermost layer of the cylinder structure from damaging the sealing layer and the corrosion-resistant layer from the external thermal stress. Therefore, the present application strengthens the corrosion resistance of each layer, fully delays the corrosion rate of each layer, and ensures the stability of each structural layer, thereby achieving a long service life of the cylinder.
[0048] The results of the sulfidation corrosion test at 900-1100°C show that, compared with a single metal alloy structure cylinder, the cylinder structure designed in the present application can greatly reduce the high-temperature sulfidation corrosion of the metal cylinder during the pre-carbonization heat treatment process of the lithium-ion battery graphite negative electrode material at 900-1100°C, greatly extending the service life of the cylinder.
[0049] In some preferred embodiments, the base layer 1 serves as the main structure of the rotary kiln cylinder, and ensures the mechanical strength and rigidity of the rotary kiln cylinder when it is heated and rotated at high temperature. Its material includes one or more of Fe-based high-temperature alloys, Ni-based high-temperature alloys and Co-based high-temperature alloys.
[0050] The thickness of the base layer 1 is ≥10 mm.
[0051] The matrix material and matrix layer thickness design of the Fe-based high-temperature alloy, Ni-based high-temperature alloy and / or Co-based high-temperature alloy ensure the stability of the matrix layer structure at high temperatures, ensuring that the cylinder body does not produce obvious bending deformation at high temperatures.
[0052] In some preferred embodiments, in order to ensure the long-term stability of the base layer 1 against external oxidation corrosion at temperatures above 1000° C., the average Ni content in the base layer 1 is ≥20%, and the average Cr content is ≥25%.
[0053] In some preferred embodiments, the Al content in the aluminized layer 11 is ≥ 15%, and the thickness of the aluminized layer 11 is 50-300 μm, which can greatly improve the corrosion resistance of the aluminized layer.
[0054] In some preferred embodiments, the bonding transition layer 2 is a bonding layer that ensures that the corrosion-resistant layer 3 does not fall off during thermal vibration, and its material includes one or more of NiCr alloy, CoCr alloy, FeCrAlY alloy, NiCrAlY alloy, CoCrAlY alloy and NiCrCoAlY alloy;
[0055] And / or, the thickness of the bonding transition layer 2 is 50-2002 μm;
[0056] And / or, the melting point of the bonding transition layer 2 is ≥1300°C;
[0057] And / or, the thermal expansion coefficient of the bonding transition layer 2 is (12-15)×10 -6 K -1 .
[0058] In some preferred embodiments, the material of the corrosion-resistant layer 3 is one or more of Al2O3, ZrO2, AlN, BN, Si3N4, SiC, NiAl alloy, CoAl alloy, AlMo alloy and AlMoSi alloy. Compared with the base layer alloy, the sulfidation corrosion rate of the corrosion-resistant layer 3 material at 900-1100°C can be reduced by 10 2 ~10 4 times.
[0059] The thickness of the corrosion-resistant layer 3 is 50-2002 μm;
[0060] The melting point of the corrosion-resistant layer 3 is ≥1400°C, and the decomposition temperature is ≥1400°C.
[0061] In some preferred embodiments, the sealing layer 4 is used to fill the holes in the corrosion-resistant layer 3 and the bonding transition layer 2 to prevent corrosive gases from penetrating the holes to corrode the base layer and the bonding transition layer 2 and cause the adhesion of the bonding transition layer 2 and the corrosion-resistant layer 3 to deteriorate and fall off. Its material includes one or more of silicone, inorganic silicone and asphalt-based aluminum paste.
[0062] The thickness of the sealing layer 4 is 30-1002 μm.
[0063] The present application also provides a method for preparing a high temperature corrosion resistant cylinder structure for heat treatment of graphite negative electrode materials, which comprises the following steps:
[0064] 101 : On the base layer 1 , aluminizing is performed by using a solid powder embedding method, so that the base layer 1 forms a base layer body 10 and an aluminizing layer 11 .
[0065] 102: sandblasting the surface of the aluminized layer 11 to achieve a designed roughness.
[0066] The designed roughness Rz can be determined according to actual needs. For example, as an example, the designed roughness Rz is 25-100 μm.
[0067] The roughening treatment of the inner surface of the base layer 1 increases the adhesion and bonding force between the base layer 1 and the bonding transition layer 2 , ensuring that the bonding transition layer 2 can be firmly bonded to the base layer 1 .
[0068] 103 : Spraying on the aluminized layer 11 by a plasma thermal spraying process to form a bonding transition layer 2 .
[0069] 104: Spraying on the bonding transition layer 2 through a plasma thermal spraying process to form a corrosion-resistant layer 3.
[0070] 105 : Spraying or brushing a sealing agent on the corrosion-resistant layer 3 , and then performing a pre-oxidation heat treatment to obtain a sealing layer 4 .
[0071] The temperature of the pre-oxidation heat treatment is 600-1050° C. The pre-oxidation heat treatment is performed at 600-1050° C. The material of the sealing layer 4 undergoes thermal decomposition, and the residual products are Al2O3 and SiO2, which fill the pores in the corrosion-resistant layer 3.
[0072] The embodiment of the present application also provides a rotary kiln, which includes a high-temperature corrosion-resistant cylinder structure for heat treatment of graphite negative electrode materials.
[0073] The present application is described below through several embodiments.
[0074] Example 1
[0075] The rotary kiln for graphite negative electrode materials of lithium-ion batteries with a heating temperature of 900-1100°C outside the carbonization section has a cylinder structure of: ① The substrate layer is 310S (0Cr25Ni20) stainless steel; ② The thickness of the substrate layer is 16mm; ③ The surface of the substrate layer is powder-aluminized at 1000°C for 1.5h, and the thickness of the aluminized layer is 100μm; ④ A 100μm thick NiCr alloy is plasma sprayed on the inside of the cylinder as a bonding transition layer; ⑤ A 150μm thick Al2O3 is plasma sprayed outside the bonding transition layer as a corrosion-resistant layer; ⑥ A 50μm organic silicon coating is brushed on the outside of the Al2O3 corrosion-resistant layer as a sealing layer; ⑦ The cylinder is first aerobically heated at 600°C for 3h, and then aerobically heated at 1050°C for 16h; ⑧ The cylinder is put into nitrogen to protect the graphite negative electrode material for pre-carbonization Working, the sulfur content of the material is 1.0-2.5%, the pre-carbonization temperature is 900-1100℃, and the cuttable parts in the cylinder are sampled and sliced for analysis regularly; ⑨ After 60 days of pre-carbonization material treatment and operation, the inner side of the rotary kiln cylinder is inspected. After inspection, the outer sealing layer structure of the cylinder inner coating is intact, the corrosion-resistant layer structure is intact, the transition layer structure is intact, the maximum S element content of the sample is 2%, the S element corrosion depth is 20μm, and the sealing coating is infiltrated; ⑩ After 180 days of pre-carbonization material treatment and operation, the inner side of the rotary kiln cylinder is inspected. After inspection, the outer sealing layer of the cylinder inner coating has a certain wear and tear, and the thickness is thinned to 20μm. The corrosion-resistant layer and transition layer structures are intact. The maximum S element content of the sample is 5%, the S element penetration depth is 60μm, and the corrosion-resistant layer is infiltrated; After 360 days of pre-carbonized material treatment, the inner side of the rotary kiln cylinder was inspected. The inspection showed that the outer sealing layer of the cylinder inner coating had aggravated wear and the thickness was reduced to 10μm. The corrosion-resistant layer and transition layer structures were intact. The maximum S element content of the sample was 32%, the S element penetration depth was 200μm, and the bonding transition layer was penetrated.
[0076] Example 2
[0077] The difference between it and Example 1 is that: ③ The thickness of the aluminized layer is 50 μm.
[0078] Example 3
[0079] The difference between it and Example 1 is that: ③ The thickness of the aluminized layer is 40 μm.
[0080] Example 4
[0081] The difference between it and Example 1 is that: ③ The thickness of the aluminized layer is 0 μm, that is, there is no aluminized layer.
[0082] Example 5
[0083] The difference between it and Example 1 is that: ④ The thickness of the bonding transition layer is 50 μm.
[0084] Example 6
[0085] The difference between it and Example 1 is that: ④ The thickness of the bonding transition layer is 30 μm.
[0086] Example 7
[0087] The difference between it and Example 1 is that: ④ The thickness of the bonding transition layer is 0 μm, that is, there is no bonding transition layer.
[0088] Example 8
[0089] The rotary kiln for lithium-ion battery graphite negative electrode material with a heating temperature of 900-1100℃ outside the carbonization section has the following cylinder structure: ① The substrate layer is 310S (0Cr25Ni20) stainless steel; ② The thickness of the substrate layer is 16mm; ③ The surface of the substrate layer is powder-aluminized at 1000℃ for 2h, and the thickness of the aluminized layer is 150μm; ④ The inner side of the cylinder is plasma-sprayed with a 100μm thick FeCrAlY alloy as a bonding transition layer; ⑤ A 150μm thick Al2O3 is plasma-sprayed outside the bonding transition layer. N as the corrosion-resistant layer; ⑥ Spray a 50μm asphalt-based aluminum slurry coating as a sealing layer at room temperature on the outside of the corrosion-resistant layer; ⑦ First, the cylinder is aerobically heated at 800℃ for 5h, and then aerobically heated at 1050℃ for 24h; ⑧ The cylinder is put into nitrogen protection for pre-carbonization of graphite negative electrode materials, the sulfur content of the material is 1.0-2.5%, and the pre-carbonization temperature is 900-1100℃; ⑨ After 90 days of pre-carbonization material treatment and operation, the inner side of the rotary kiln cylinder is inspected. After inspection, the outer sealing layer structure of the inner coating of the cylinder is intact, the corrosion-resistant layer structure is intact, and the transition layer structure is intact, without obvious corrosion; ⑩ After 270 days of pre-carbonization material treatment and operation, the inner side of the rotary kiln cylinder is inspected. After inspection, the outer sealing layer of the inner coating of the cylinder has a certain wear and tear, and the thickness is thinned to 13μm. The corrosion-resistant layer and transition layer structures are intact; After 360 days of pre-carbonized material treatment, the inner side of the rotary kiln cylinder was inspected. The inspection showed that the thickness of the outer sealing layer of the cylinder inner coating was reduced to 7μm, and the corrosion-resistant layer and transition layer structures were intact.
[0090] Example 9
[0091] The rotary kiln for lithium-ion battery graphite negative electrode material has an external heating temperature of 900-1100°C in the carbonization section. The cylinder structure of the carbonization section is as follows: ① The substrate layer is 602CA high nickel alloy; ② The thickness of the substrate layer is 16mm; ③ The cylinder is not treated with any corrosion protection; ⑦ The cylinder is put into nitrogen protection for pre-carbonization of graphite negative electrode material, the sulfur content of the material is 0.5-1.5%, and the pre-carbonization temperature is 900-1100°C; ⑧ After 60 days of pre-carbonization material treatment operation, the inner side of the rotary kiln cylinder is inspected. The average corrosion depth of the inner side of the cylinder is about 5mm, and the maximum corrosion depth is 8mm.
[0092] The cylinder structures of the above-mentioned embodiments were put into nitrogen protection graphite negative electrode material pre-carbonization work, the sulfur content of the material was 0.5-1.5%, the pre-carbonization temperature was 950-1050°C, and the corrosion of the cut surface structure of the sample in the cylinder structure was tested at different pre-carbonization times (60 days, 90 days, 180 days, 270 days and 360 days). The results are shown in Table 1 below:
[0093] Table 1
[0094]
[0095]
[0096]
[0097] Note: The corrosion depth is calculated from the outer surface of the sealing layer downwards, regardless of whether the layers fall off.
[0098] From the corrosion results in Table 1 above, we can see that:
[0099] Since the sealing layer and the corrosion-resistant layer are not completely dense and have through holes inside, hydrogen sulfide gas will pass through the sealing layer and the corrosion-resistant layer to slowly corrode the bonding transition layer, that is, sulfur gradually migrates into the interior of the transition layer, while metal ions migrate from the transition layer to the outside of the corrosion-resistant layer and the sealing layer; the metal ions and sulfur that migrate to the outer surface of the sealing layer form a sulfide corrosion layer; at the same time, the sulfur elements and metal ions that migrate to the bonding transition layer form corrosion products, sulfides, inside the bonding transition layer; as the corrosion time increases, the bonding transition layer produces a certain amount of sulfur and metal ion migration channels, and the ion migration depth exceeds the thickness of the bonding transition layer, and the sulfur migrates to the aluminized layer, and the metal ions in the aluminized layer migrate to the bonding transition layer and the outer layers; since the migration speed of sulfur in the aluminized layer is much lower than that of the substrate layer, the period of damage to the aluminized layer by sulfidation corrosion is prolonged; similar to the sulfidation corrosion process of the bonding transition layer, when sulfur penetrates the aluminized layer, the substrate layer begins to be corroded by sulfidation.
[0100] Although the sealing layer and the corrosion-resistant layer have extremely small reaction rates, and hydrogen sulfide has little destructive effect on the sealing layer and the corrosion layer, the sulfide corrosion products formed on the surface of the sealing layer will undergo thermal stress shedding due to temperature changes, and the corrosion products will carry the sealing layer with them when they shelve off. Similarly, when the bonding transition layer is severely corroded, the internal corrosion product sulfide will also shelve due to thermal stress, and the bonding transition layer will also shelve off. The shedding of the bonding transition layer will cause the corrosion-resistant layer and the sealing layer attached to it to fall off together. The situation of the aluminized layer is similar. When the aluminized layer is severely corroded and shedding occurs, the bonding transition layer, the corrosion-resistant layer and the sealing layer attached to it will all fall off together.
[0101] To summarize, in the cylinder structure designed in the present application, the functions of each layer are interdependent. The sealing layer and the corrosion-resistant layer are used to shield the external hydrogen sulfide from penetrating into the bonding transition layer. The bonding transition layer is used to ensure the adhesion stability of the corrosion-resistant layer. The aluminized layer slows down the unstable shedding of the bonding transition layer caused by the corrosion of the base layer. At the same time, the aluminized layer also reduces the outward migration rate of the base metal ions, thereby preventing the corrosion products generated in the outermost layer of the cylinder structure from damaging the sealing layer and the corrosion-resistant layer from the external thermal stress. Therefore, the present application strengthens the corrosion resistance of each layer, fully delays the corrosion rate of each layer, and ensures the stability of each structural layer, thereby achieving a long service life of the cylinder.
[0102] In the description of the present application, it should be noted that the terms "upper", "lower", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application. Unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be an indirect connection through an intermediate medium, or it can be a connection between the two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the present application can be understood according to the specific circumstances.
[0103] It should be noted that, in this application, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the presence of other identical elements in the process, method, article or device including the elements.
[0104] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A high temperature corrosion resistant cylinder structure for heat treatment of graphite negative electrode material, characterized in that: The invention comprises a base layer (1), a bonding transition layer (2), a corrosion resistant layer (3) and a sealing layer (4) which are arranged in sequence, wherein the base layer (1) comprises a base layer body (10) and an aluminized layer (11) formed on the surface of the base layer body (10), the aluminized layer (11) is located between the base layer body (10) and the bonding transition layer (2), and the thermal expansion coefficient of the bonding transition layer (2) is between the thermal expansion coefficients of the base layer (1) and the corrosion resistant layer (3).
2. The high temperature corrosion resistant cylinder structure for heat treatment of graphite negative electrode material according to claim 1, characterized in that: The material of the substrate layer (1) includes one or more of Fe-based high-temperature alloy, Ni-based high-temperature alloy and Co-based high-temperature alloy; And / or, the thickness of the base layer (1) is ≥10 mm.
3. The high temperature corrosion resistant cylinder structure for heat treatment of graphite negative electrode material according to claim 1, characterized in that: The average Ni content in the base layer (1) is ≥20%, and the average Cr content is ≥25%.
4. The high temperature corrosion resistant cylinder structure for heat treatment of graphite negative electrode material according to claim 1, characterized in that: The Al content in the aluminized layer (11) is ≥ 15%; And / or, the thickness of the aluminized layer (11) is 50-300 μm.
5. The high temperature corrosion resistant cylinder structure for heat treatment of graphite negative electrode material according to claim 1, characterized in that: The material of the bonding transition layer (2) includes one or more of NiCr alloy, CoCr alloy, FeCrAlY alloy, NiCrAlY alloy, CoCrAlY alloy and NiCrCoAlY alloy; And / or, the thickness of the bonding transition layer (2) is 50-2002 μm; and / or, the melting point of the bonding transition layer (2) is ≥ 1300° C.; And / or, the thermal expansion coefficient of the bonding transition layer (2) is (12-15)×10 -6 K -1 .
6. The high temperature corrosion resistant cylinder structure for heat treatment of graphite negative electrode material according to claim 1, characterized in that: The material of the corrosion-resistant layer (3) is one or more of Al2O3, ZrO2, AlN, BN, Si3N4, SiC, NiAl alloy, CoAl alloy, AlMo alloy and AlMoSi alloy; and / or, the thickness of the corrosion-resistant layer (3) is 50-2002 μm; And / or, the melting point of the corrosion-resistant layer (3) is ≥1400°C, and the decomposition temperature is ≥1400°C.
7. The high temperature corrosion resistant cylinder structure for heat treatment of graphite negative electrode material according to claim 1, characterized in that: The material of the sealing layer (4) includes one or more of organic silicon, inorganic silicon and asphalt-based aluminum paste; And / or, the sealing layer (4) has a thickness of 30-1002 μm.
8. A method for preparing a high temperature corrosion resistant cylinder structure for heat treatment of graphite negative electrode materials as claimed in any one of claims 1 to 7, characterized in that: It includes: Aluminizing the base layer (1) by solid powder embedding method, so that the base layer (1) forms a base layer main body (10) and an aluminized layer (11); The surface of the aluminized layer (11) is subjected to sandblasting treatment so as to achieve a designed roughness; Spraying on the aluminized layer (11) by a plasma thermal spraying process to form a bonding transition layer (2); Spraying on the bonding transition layer (2) through a plasma thermal spraying process to form a corrosion-resistant layer (3); A sealing agent is sprayed or brushed on the corrosion-resistant layer (3), and then a pre-oxidation heat treatment is performed to obtain a sealing layer (4).
9. The method for preparing the high temperature corrosion resistant cylinder structure for heat treatment of graphite negative electrode material according to claim 8, characterized in that: The designed roughness Rz is 25-100 μm; And / or, the temperature of the pre-oxidation heat treatment is 600-1050°C.
10. A rotary kiln, characterized in that: It comprises a high temperature corrosion resistant cylinder structure for heat treatment of graphite negative electrode materials as claimed in any one of claims 1 to 7.